ADHD and Psychoactive Substance Use Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The association between attention deficit/hyperactivity disorder (ADHD) and psychoactive substance use disorders (PSUD) was studied by familial risk analysis at the Massachusetts General Hospital, Boston, MA.